An Investigation of Lexical Cohesion on Indonesian Singer Song - Ahmad Murodi; Didin Nuruddin Hidayat; Alek Alek (Universitas Cokroaminoto Palopo, 2021)
This paper sheds light on investigating the lexical cohesion on an Indonesian singer song entitled Coke Bottle by Agnez Mo. Lexical cohesion constitutes linguistic devices that help to create cohesiveness of the text. Lexical cohesion occurs when two words or more in a text are semantically related somehow – in other words, they are related in terms of their meaning. This study's design was a descriptive qualitative that attempted to elaborate the discourse analysis about lexical cohesion in Coke Bottle song by Agnez Mo. Some steps were conducted to collect the data, firstly, the lyrics that become the documentation were collected by the researcher from lyrics.com, secondly the researcher read the lyrics to understand the text. Thirdly, marking some words included as lexical cohesions in which they will be the real data of this study. The findings revealed that reiteration and collocation are found in the song, but the antonym that is part of reiteration is absent. Above all, repetition is the most commonly used in this song, especially the word I. This seems to indicate that the songwriter tried to make the song's lyrics match the music's beat, so the song became easy listening, and the listeners can enjoy the music.